Reducing surface and subsurface water flow effect on gullies through low cost measures [Abstract only] - Addisie, Meseret B.; Ayele, Getaneh K.; Gessesse, A.A.; Tilahun, Seifu A.; Zegeye, Assefa D.; Moges, M.; Schmitter, Petra S.; Langendoen, E.J.; Steenhuis, Tammo S. (2015)
Gully erosion in the humid Ethiopian highlands intensified in recent decades. The study was conducted in the Birr watershed located south west of Bahir Dar the capital of Amhara regional state, Ethiopia. We studied 14 gullies having similar morphology at three sub watersheds. The watershed covers a total area of 414 ha. The monitoring continued over the 2013 to 2014 monsoon season to better understand the factors controlling gully erosion and the effectiveness of erosion control structures. Perched ground water table was measured at the gully heads and erosion pins were installed to monitor the rate of recession from uncontrolled heads. Though soil properties, ground cover, gully morphology had small contribution for the gully development; water fall effect at the head of the gully and elevated water table depth at both heads and banks played the key role. Therefore the study focused on reducing the water fall and elevated water table effect by applying two low cost gully control approaches. The first approach was regrading the gully heads and banks at 45o and the second approach follows regrading the gully heads at 45o and putting a graded type of stone rip rap. Large stones were anchored at the toe of the head maintaining the stable gully bed slope. The result shows that unprotected gully heads retreat an average of 4m which is equivalent to 37m3 volume of soil loss. The maximum and minimum head cut retreat was between 0 and 22.5m. The total area damaged by annual gully head retreat was 240m2 and total volume of soil lost was 444m3. The treated gully heads did not show any retreat during the monitoring period. Compared with simple reshaping of gully heads, integration with Stone rip rap was an effective and low cost measure in the study watershed. Plantation could not stop the upslope migration of heads though it had the potential to trap sediments down slope. Heads with stone rip rap allows fast re vegetation whereas unprotected reshaped heads and banks took longer time to re vegetate and stabilized. Time of reshaping was important for the stability of banks and heads.